Adsorption Capacities of Hygroscopic Materials Based on NaCl-TiO2 and NaCl-SiO2 Core/Shell Particles. (13th February 2020) - Bermeo, Marie; El Hadri, Nabil; Ravaux, Florent; Zaki, Abdelali; Zou, Linda; Jouiad, Mustapha
Abstract : Hygroscopic materials which possess high moisture adsorption capacity were successfully upgraded by the functionalization of sodium chloride (NaCl) using two nuances of oxides. A procedure was developed to first prepare submicron-sized NaCl crystals; thereafter, these crystals were coated by choice of either titanium dioxide (TiO2 ) or silica (SiO2 ) to enhance the hygroscopic properties of NaCl and prevent its premature deliquescence. After coating, several analytical techniques were employed to evaluate the obtained composite materials. Our findings revealed that both composites NaCl-TiO2 and NaCl-SiO2 gave excellent performances by exhibiting interesting hydrophilic properties, compared to the sole NaCl. This was demonstrated by both environmental scanning electron microscope (ESEM) and water vapor adsorption experiments. In particular, NaCl-TiO2 composite showed the highest water adsorption capacity at low relative humidity and at a faster adsorption rate, induced by the high surface energy owing to the presence of TiO2 . This result was also confirmed by the kinetics of adsorption, which revealed that not only does NaCl-TiO2 adsorb more water vapor than NaCl-SiO2 or sole NaCl but also the adsorption occurred at a much higher rate. While at room temperature and high relative humidity, the NaCl-SiO2 composite showed the best adsorption properties making it ideal to be used as a hygroscopic material, showing maximum adsorption performance compared to NaCl-TiO2 or sole NaCl. Therefore, NaCl-TiO2 and NaCl-SiO2 composites could be considered as promising hygroscopic materials and potential candidates to replace the existing salt seeding agents.